2019
DOI: 10.1002/hep4.1425
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Risk Factors for Hepatic Encephalopathy in a Population‐Based Cohort of Americans With Cirrhosis

Abstract: Hepatic encephalopathy (HE) is a devastating complication of cirrhosis. Data are limited regarding the incidence of and risk factors for HE among contemporary patients in the context of the shifting epidemiology of cirrhosis. We examined a 20% random sample of U.S. Medicare enrollees with cirrhosis and Part D prescription coverage from 2008 to 2014. We modelled incident HE using demographic, clinical, and pharmacologic data. Risk factors for HE were evaluated, including demographics/socioeconomics, cirrhosis e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 50 publications
4
98
0
4
Order By: Relevance
“…For instance, it may be that opioid‐induced altered mental status is being misdiagnosed as HE. However, the annual incidence of HE and other decompensation events are comparable to what has been published in the literature, providing external validity to our results . In addition, any event prompting a billing code for HE or the initiation of lactulose/rifaximin is likely to be clinically important.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For instance, it may be that opioid‐induced altered mental status is being misdiagnosed as HE. However, the annual incidence of HE and other decompensation events are comparable to what has been published in the literature, providing external validity to our results . In addition, any event prompting a billing code for HE or the initiation of lactulose/rifaximin is likely to be clinically important.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings add to the data from Medicare demonstrating that opioids are associated with an increased risk of HE . This Medicare study included a much older population than our current study and did not limit their population to those with well‐compensated cirrhosis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This demonstrates the considerable risk of chronic opioid use among patients newly discharged on opioid therapy after hospitalization. Opioid use in patients with cirrhosis has also been associated with an increased risk of hepatic encephalopathy [27,28], health care utilization [5], hospital readmissions [6], respiratory depression or overdose [29], and decreased health-related quality of life [30].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 We found that opioid prescriptions are independently associated with incident HE in younger patients with well compensated cirrhosis, 2 validating similar findings from the US Medicare population. 5 This adds to many other potential harms of opioids in cirrhosis, including hospital readmissions, 6 overdose 7 and decreased health-related quality of life. 8 Furthermore, in a recent randomized trial of treatments for osteoarthritis and back pain, patients receiving opioids reported increased pain compared to the non-opioid group 9 and, in cirrhosis, opioid use is associated with greater pain-related disability, even when adjusting for the severity of pain.…”
Section: Editorsmentioning
confidence: 99%